أنشطة الأعمال ودور المشاريع الصغيرة والمتوسطة "SME’s" في زيادة الناتج المحلي الإجمالي في سورية " GDP" - سلمان حيان (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يتناول هذا البحث إبراز أنشطة الأعمال ودور المشاريع الصغيرة والمتوسطة في الاقتصاد الوطني، والدور المأمول لهذا القطاع في زيادة النشاط الاقتصادي، وتأمين فرص العمل، وزيادة الناتج المحلي الإجمالي عموماً. ومن خلال تحليل واقع هذا القطاع، تم التركيز على أهم الخصائص والمميزات لقطاع المشاريع الصغيرة والمتوسطة في سورية، بالإضافة إلى استعراض أهم نقاط الضعف التي تواجه الاقتصاد الوطني عموماً، وهذا القطاع بشكل خاص. ومنها تم اشتقاق العديد من المقترحات التي تسهم في النهوض، وتطوير بيئة الأعمال والمشروعات الصغيرة والمتوسطة، وبما يسهم في تعزيز ودعم دورها في الاقتصاد الوطني. This research highlight the business activities and the role of small and medium-sized enterprises SME’s in the national economy, and expectancy role of this sector is increasing economic activity, securing jobs and increasing gross domestic product GDP in general. It also focuses on the most important characteristics and features of the sector of SME’s in Syria. In addition to review of the main weaknesses facing the national economy in general and this sector, in particular, which contributed to the derivation of many suggestions contribute to the advancement and development of business environment and SME’s and to the promotion and support its role in national economy.